Extended analysis of the FTIR high–resolution spectrum of D232S in the region of the ν2 band. (February 2019) - Sydow, C.; Ulenikov, O.N.; Bekhtereva, E.S.; Gromova, O.V.; Glushkov, P.A.; Maul, C.; Bauerecker, S.
Highlights: High resolution analysis of D2 S FTIR spectra. The ν 2 band: line positions and strengths. Determination of spectroscopic parameters. Abstract: The high resolution infrared spectra of dideuterated hydrogen sulfide D2 S were recorded with a Bruker IFS 125HR Fourier transform infrared spectrometer (Zürich prototype ZP2001) and analyzed in the ν 2 fundamental band region, 750–1200 cm − 1 . The 1742 transitions (which is more than two times more than in the preceding analogous studies) were assigned in the experimental spectra to the ν 2 band (the maximum values of the quantum numbers are J max = 30 and K a max = 21 ). The subsequent weighted fit of experimentally assigned transitions was made with the Watson Hamiltonian, resulting in a set of 34 parameters which reproduces the initial 535 infrared ro–vibrational energy values from 1742 experimental line positions with a root mean square deviation d r m s = 1.31 × 10 − 4  cm − 1 . An analysis of 280 experimental ro–vibrational line intensities (324 transitions) of the ν 2 band was made using the Hartmann–Tran profile of individual lines, and the results were applied then in the fit of parameters of the effective dipole moment operator. Isotopic relations for the dipole moment parameters were derived and used for the fit procedure. The obtained "model dependent" parameters reproduce the initial line strengths with the d r m s = 2.5 % . A list of 1742 experimental transitions of D2 S is generated together with the presentation of their individual line strengths calculated on the basis of the obtained effective dipole moment parameters.